2020
DOI: 10.3329/bsmmuj.v13i1.45052
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum progesterone level in preeclampsia

Abstract: a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Progesterone is primarily produced by the placenta after the eighth week of gestation (Pylypchuk and Pylypchuk 2021 ), and the abundant immuno-expression of P and PRs in normotensive placental tissue is expected. The decrease of P observed in our study is corroborated by several studies that noted lower circulating levels of P in PE, suggesting a hormonal deficiency in PE (Iou et al 2005 ; Kiprono et al 2013 ; Wan et al 2018 ; Chowdhury et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Progesterone is primarily produced by the placenta after the eighth week of gestation (Pylypchuk and Pylypchuk 2021 ), and the abundant immuno-expression of P and PRs in normotensive placental tissue is expected. The decrease of P observed in our study is corroborated by several studies that noted lower circulating levels of P in PE, suggesting a hormonal deficiency in PE (Iou et al 2005 ; Kiprono et al 2013 ; Wan et al 2018 ; Chowdhury et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Data analysis revealed no statistically significant difference between two groups patients in terms of sociodemographic parameters (p>0.05) but about 80% patients both case and controlled group come from lower and lower middle class family. In accordance with Chowdhury et al [15] reported the mean age and socioeconomic condition of the participants with or without preeclampsia were 27.1±5.2 years and 25.8±4.5 years, respectively (p=0.271) and 53.3 and 72.9% belonged to the middle class. The body mass index of 46.7% from the experimental group and 41.7% from the control group were ≥25 kg/m2, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…In 2020, also in Bangladesh, another study conducted by Chowdhury et al found significantly higher fT levels in pre-eclamptic women by the end of gestation when compared to the control [ 92 ]. During the same year, in Taiwan, Lan’s research group discovered similar T levels in the umbilical cords of both groups.…”
Section: Effects Of Testosterone In Pre-eclampsiamentioning
confidence: 99%